Employee engagement: A study on gen Y in the manufacturing industry - Chee, Wee Tee; Yahya, Khulida Kirana; Johari, Johanim (2017)
Today’s engaged employees have become a crucial issue in this business world.Recruiting and engaging employees are the main concern for employers today.Gen Ys gradually dominating the workforce in the future, thus employers prepare to transform some of their policies and system to fit with their characteristics such as flexibility in workplace and equilibrium the rewards with their efforts.This study was focus on the Malaysian manufacturing industry which is the main contributor to the country GDP.The employees of the industry mainly comprised of Gen Ys and are known to be less engaged.There are many factors that lead to employee engagement.This study will look at factors that influence employee engagement, namely compensation and work-life balance. A survey was carried out among employees of manufacturing industry where 1000 questionnaires were distributed but only 996 were returned and utilized for data analysis. Regression analysis results indicate that compensation and work life balance were have significant relationship with employee engagement.